Development of an ESQ integrated e-book on biodiversity to increase student’s motivation and character - Zulgusma Aulia Putri; Z. Zulyusri; S. Syamsurizal; V. Vauzia; Fitri Arsih (University of Muhammadiyah Malang, 2025)
Education plays an important role in developing students' potential, including character building. However, biology learning so far has focused more on the cognitive aspect, while emotional intelligence (EQ) and spirituality (SQ) have received less attention. The learning media used is also not interesting and has not integrated ESQ values. This study aims to develop an ESQ-integrated biology e-book on biodiversity material for Phase F students that is valid, practical, and effective. The type of research used is Research and Development (R&D) with the ADDIE model (Analyse, Design, Develop, Implement, and Evaluate). The research instruments included teacher interviews, validity questionnaires, practicality, as well as motivation and character questionnaires for students. The e-book was validated by expert lecturers and biology teachers, and tested for practicality and effectiveness at State Islamic Senior High School 2 Tanah Datar. The validation results showed that the e-book was very valid (93.14%) and very practical (95.15%). The increase in motivation and character in the experimental class was significant, with N-gain scores of 79.26% and 77.45%, respectively. So, this e-book is worth using as a biology learning media that not only improves understanding, but also the character and motivation of students.